Analysis of Risk Factors For Dry Eye Disease Among Educational Staff of The Faculty of Medicine, Muslim University of Indonesia Using The Ocular Surface Disease Index (OSDI) Questionnaire - Vadya Hidayanti; Ratih Natasha Maharani; Zulfikri Khalil Novriansyah; Suliati P Amir; Nur Aulia Amir (Jurnal Medisci, 2026)
Background: Dry eye disease is a common ocular health problem that can impair comfort, visual performance, and work productivity, particularly in occupational environments. Aim: This study aimed to analyze factors associated with the occurrence of dry eye disease among educational staff at the Faculty of Medicine, Universitas Muslim Indonesia. Methods: An analytical cross-sectional study was conducted using structured questionnaires and standardized symptom assessment to evaluate sex, age, duration of digital device use, air conditioner exposure, smoking habits, and dry eye disease status, followed by bivariate and multivariate statistical analyses. Results: Smoking habits and air conditioner exposure were associated with a statistically significant increase in the occurrence of dry eye disease. Age did not demonstrate a significant association but tended to aggravate the effects of other risk factors. Sex and duration of digital device use were not significantly associated with dry eye disease; however, female sex and excessive digital device use appeared to increase susceptibility. Conclusions: Environmental and lifestyle factors, particularly smoking exposure and prolonged use of air conditioners, play an important role in the development of dry eye disease among educational staff. Implication: These findings highlight the need for preventive strategies that improve workplace environmental conditions and promote healthier lifestyle behaviors to reduce the burden of dry eye disease in occupational settings.